2020
DOI: 10.21203/rs.3.rs-19902/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental disorder and PTSD in Syria during wartime: a national-wide crisis

Abstract: Background: Syria has experienced war over the past seven years, leaving a high percentage of the population below the poverty line. This has significantly impacted Syrians which is reflected in the psychiatric aspect. This study evaluates the severity of the mental disorder caused by war and other factors, and evaluates the post-traumatic stress disorder (PTSD) in addition to support provided to Syrians. Methods: Online surveys including the Kessler 10 (K10) survey, the Screen for Posttraumatic Stress Symptom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 33 publications
0
29
2
Order By: Relevance
“…Higher prevalence of PTSD was found in people who encountered a traumatic event and/or were exposed to the war in Syria [4]. PTSD symptoms lead to considerable impairment and severely disrupt social, occupational, and educational performance and functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher prevalence of PTSD was found in people who encountered a traumatic event and/or were exposed to the war in Syria [4]. PTSD symptoms lead to considerable impairment and severely disrupt social, occupational, and educational performance and functioning.…”
Section: Introductionmentioning
confidence: 99%
“…While there has been some attention to rates of PTSD in Syria [4], few studies have been concerned with the status of children [11][12][13]. These studies found that higher social support was correlated with a lower probability of having PTSD [4,14]. However these existing studies suffer from considerable limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Another theory is that as allergic rhinitis is very common in Syria (11), and that allergic rhinitis and LPR may be correlated (24) which could explain this nding. We also speculate that the high psychological stress that Syrians face with high prevalence of severe mental disorder from war (12), this could cause dyspepsia and exaggerating of GORD symptoms which can mimic LPR. Similarly, we found in our study that being distressed from war noises was correlated with a higher frequency for LPR, suggesting that quality of life and psychological factors could also have contributed to our ndings.…”
Section: Discussionmentioning
confidence: 91%
“…In patients with LPR, males comprised of 20.5% (CI 95%: 15.4-26.1), females comprised of 79.5% (CI 95%: 73.9-84.6), cigarette smoking comprised of 21.4% (CI 95%: 16.2-26.9) shisha smoking comprised of 33.3% (CI 95%: 27.4-39.7), subjects with asthma comprised of 4.3% (CI 95%: 2.1-7.3), and subjects with allergic reactions comprised of 8.1% (CI 95%: 4. [7][8][9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation